Penyuluhan Mengenai Pengolahan Sampah Organik Berbasis Eco Enzyme Bagi PKK Banjar Pesurungan Kusamba Bali - Desak Made Febri Purnama Sari; Kadek Ayu Maysia Danalia Mas; Ida Ayu Oka Martini (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2024)
Counseling on Eco Enzyme Based Organic Waste Processing for PKK village meeting hall Pesurungan Kusamba Bali. The population of Klungkung district has always increased from time to time, especially in urban areas. The increase in demand caused by the increasing population in Klungkung Regency has implications for the volume of waste disposed of. In implementing this work program, using the lecture or counseling method. Counseling using an LCD projector with the theme of my work program, namely Counseling on eco-enzyme-based organic waste processing, invited 40 PKK village meeting hall Pesurungan, Kusamba Village, Klungkung Regency, Bali Province. The resource person explained material on how to process organic waste into eco enzymes and carried out the practice of making eco enzymes to get a positive response. With this extension work program they can process waste properly and correctly and they can practice directly at their respective homes to make eco-enzyme that is environmentally friendly. The specialty of eco enzyme is that it does not require large areas of land for the fermentation process such as in the composting process. Making eco enzyme is very economical in terms of processing area and can be applied at home.